Characterization Crude Palm Oil (CPO) Olein Fraction As A Raw Material for Cooking Oil - Jusman Jusman; Syamsuddin (UNIB Press, 2023)
Research has been carried out on the characterization of crude palm oil olein fraction as a raw material for cooking oil. In the initial stage, crude palm oil is centrifuged at 4000 rpm for 30 minutes to separate the olein and stearin fractions from crude palm oil. Then the olein fraction is treated using rice husk ash to obtain an olein fraction that meets the standard raw materials for making cooking oil. Therefore, the olein fraction was characterized by measuring several parameters including water content, free fatty acid content, carotenoid content and peroxide value. The results of research on water content are in the range of 0.02 – 0.07% , free fatty acid content is in the range of 0.03 – 0.08%, and peroxide content is in the range of 0.14 – 0.16 meq/kg. Results of research on the characterization of the crude palm oil olein fraction shows parameters that are a reference in determining the quality of cooking oil raw materials that meet the required standards.